Pengaruh Kualitas Pelayanan Dan Inovasi Pelayanan Terhadap Kepuasan Pelanggan Di Bandar Udara Internasional Halim Perdana Kusuma - Jakarta - Nurwan Esacipta August; Dwi Agustina; Winda Wulandari; Sad Dian Utomo; Achmad Barlian (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
The Influence of Service Quality and Service Innovation on Customer Satisfaction at Halim Perdana Kusuma International Airport - Jakarta. Wurwan Esacipta August. NPM: CA191221683. This research aims to determine and analyze the influence of service quality and service innovation on customer satisfaction at Halim Perdana Kusuma International Airport-Jakarta. This is based on problems where there are 3 reasons behind the decrease in the number and dissatisfaction of passengers, namely: 1) High ticket prices r 2 Geographical location causing flooding, so airport operations are totally suspended; 3) Pandemic. This research was conducted at Halim Perdana Kusuma International Airport, Jakarta from March 2021 to July 2021. This research used a quantitative approach. Data was collected by distributing questionnaires to 100 service, innovation and customer satisfaction. The results show that there is a significant influence by the service quality variable on the customer satisfaction variable by 60%, there is a significantlq- influence by the service innovation variable on customer satisfaction variable by 55.1%, and there is a positive and significant influence given by the variables of service quality and service innovation together on customer satisfaction at Halim Perdana Kusuma International Airport - Jakarta by 68.2%.